Intonation and Sentence Type Conventions: Two Types of Rising Declaratives. (3rd April 2018) - Jeong, Sunwoo
Abstract: This paper presents an experimental study that provides evidence for the existence of two types of rising declaratives in English which differ systematically in their forms and their functions. The two are labelled assertive rising declaratives and inquisitive rising declaratives, respectively. Guided by the experimental results, the paper develops a semantic analysis of them. Having as backdrop an extended Lewisian model of discourse involving a conversational scoreboard, the analysis associates assertive and inquisitive rising declaratives with distinct sets of context-changing conventions that bring about fundamentally different updates to core elements of the context. In the process, it highlights their respective partial overlaps with the conventions for two other sentence types, falling declaratives and polar interrogatives. The analysis fully captures the experimental results presented in the paper and reconciles disparate, seemingly contradictory observations about English rising declaratives noted in previous work.